Estudio, diseño geométrico y estructural de la vía Curtincápac - Los Llanos - San Francisco, cantón Portovelo, provincia de El Oro. - Vera Jumbo, Carlos Alberto (2015)
The Curtincapac and Los Llanos Portovelo Canton province of Oro, site there is now a road in poor condition and that in times of winter the transfer of agricultural products and so it is impossible to exempt residents of basic services. The main objective is to conduct studies and geometric and structural design via Curtincapac - Los Llanos - San Francisco, to improve transportation, trade and education of these sectors. The parameter involved in the geometric design of the road is the topography and the amount of vehicles on this; for which, adopt the provisions Vials Reporting Standards (NEVI-2012), for the design of the tread use the AASHTO Guide for Design of Pavement Structures, 1993 edition. The characteristics of the mountainous terrain, a road of IV order, whose length is 4,570 km, with a design speed of 25 km / h was designed. The pavement structural package is 75 cm., The asphalt of 5 cm to 20 cm base, sub-base of 50 cm. For the development of the communities involved all the factors of the project are focused on a single fixed goal, which meet technical and professional criteria, prepared to meet and prioritize the most important needs in the area.